2022
DOI: 10.1101/2022.12.15.520651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple pathways for reestablishing PAR polarity inC. elegansembryo

Abstract: Asymmetric cell divisions, where cells divide with respect to a polarized axis and give rise to daughter cells with different fates, are critically important during development. In many such divisions, the conserved PAR polarity proteins accumulate in distinct cortical domains in response to a symmetry breaking cue. The one-cell C. elegans embryo has been a paradigm for understanding mechanisms of PAR polarization, but much less is known about polarity reestablishment during subsequent divisions. Here, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Based on the enhanced rate of P1 defects in arx-2; mom-5 double mutants, branched actin is likely required in a parallel pathway for either spindle positioning or PAR polarity. It has recently been shown that PAR polarity in the P1 cell is established through redundant mechanisms, at least one of which involves the actomyosin skeleton (Koch and Rose, 2023; Ng et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the enhanced rate of P1 defects in arx-2; mom-5 double mutants, branched actin is likely required in a parallel pathway for either spindle positioning or PAR polarity. It has recently been shown that PAR polarity in the P1 cell is established through redundant mechanisms, at least one of which involves the actomyosin skeleton (Koch and Rose, 2023; Ng et al, 2023).…”
Section: Discussionmentioning
confidence: 99%